Pengaruh corporate social responsibility, ROA, leverage, size terhadap agresivitas pajak - Della Dwi Rahayu; Eko Wahjudi (Jurnal Riset Pendidikan Ekonomi, 2022)
The purpose of this research is to analyze the effect of corporate social responsibility, ROA, Leverage, and Size on tax aggressiveness which is proxied by effective tax rate. This research uses a purposive sampling method by setting several criteria and uses secondary data, namely data on manufactured companies listed in IDX on period 2019, getting the results of 33 companies, data is obtained through access to the official IDX and NCSR websites, this research uses multiple linear regression analysis. The results of the research showed significant and positive effect results between the economic, environmental, social dimensions of CSR on tax aggressiveness, variable ROA, and size also showed significant and positive effect results on tax aggressiveness, while the result of leverage on tax aggressiveness is showed significant and negative effect.